Models and Algorithms for the Diagnosis of Parkinsons Disease and Their Realization on the Internet of Things Network (Global Journals of Research in Engineering, 2024)
This article aims to investigate an innovative approach utilizing model algorithms and IoT technology for early Parkinson s disease detection It introduces the comprehensive IoT network that has the IoT platform enabling the collection of voice data via mobile phones extraction of relevant features and data processing Within this process a Fully Connected Neural Network FCNN model is employed to calculate the probability of Parkinson s disease potentially providing healthcare professionals and patients with a convenient accurate and early diagnostic tool The study delves into the structure algorithms and the integral role of the FCNN within the IoT network emphasizing its potential impact on the healthcare sector
Keywords: parkinson's disease; IoT technology; early detection; voice data; noise reduction; fully connected neural network; IT-diagnosis